COGNITIV-SEMANTIC POTENTIAL OF DERIVATIVE (on material of verbs of the Polish language) - Ris-Vikers, Ulyana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article highlights the cognitive aspect of word-building structure of the word formation revealing cognitive and mental substance of the derivation phenomenon caused by the productivity of word formation model.